Additive manufacturing technologies : 3D printing, rapid prototyping, and direct digital manufacturing /: 3D printing, rapid prototyping, and direct digital manufacturing. (2015) - Gibson, Ian; Rosen, David; Stucker, B (Brent)
No abstract available